Sekilas tentang Dayak [Pangin] Orung Da’an di Desa Nanga Raun Kabupaten Kapuas Hulu - Gustaf Hariyanto; Sutami, Florensius; Florentina (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
The primary aim of this research article is to thoroughly explore and articulate the significance of Dayak Orung Daan within the diverse Dayak tribes in Kapuas Hulu, West Kalimantan. Dayak Orung Daan embodies invaluable cultural, historical, and traditional wisdom that must be conserved and seamlessly integrated into human cultural life systems. This integration is imperative in light of the potential erosion of cultural values amidst rapid development. The article seeks to illuminate the socio-cultural dimensions of Dayak Orung Daan, encompassing both historical and contemporary perspectives. The study employed ethnographic methods, including observations, resident interviews, and document and literature analysis. The research revealed substantial socio-cultural wealth in the life, history, belief systems, and philosophy of Dayak Orung Daan. Furthermore, it highlighted the enduring presence of cultural traditions governing the social order of the Dayak Orung Daan community amid social disruption. Keywords: Dayak Orung Daan, socio-cultural, disruption